Evaluación del comportamiento fenotípico y agronómico de ocho variedades de girasol “helianthus annuus” en el cantón machala - Vasquez Lopez, Bianca Estefania (Machala : Universidad Técnica de Machala, 2021)
Sunflower (Helianthus annuus L.) is an herbaceous plant of the asteraceous family of great agricultural importance at commercial level for its attractive inflorescence and its great variety of colors ranging from classic yellow to intense orange and red, as well as its beauty when following the sun during its floral development, making the sunflower crop a plant of great ornamental value. The objective of this work is to evaluate the phenotypic and agronomic performance of 8 varieties of "Helianthus annus" in Machala. The present work was carried out in the canton Machala El Oro, performing two sowings of sunflower the first was carried out in the period from August to November 2020 and the second sowing in December of the same year to March 2021 where the sunflower varieties were cultivated which were: Sunbright or Sunbeam, Moulin Rouge, Sunspot or Big Smile, Russian Giant, Velvet Queen, Common Sunflorwer, Music Box or Pastiche and Moonwalker, the study area has the coordinates of longitude O79°57'37. 91" latitude S3°15'31", 19 morphoagronomic variables were carried out in the course of its development, which were characterized by growth analysis techniques and yield variables, were estimated by means of numbers and weight of each chapter and seeds, the variables to be measured were: peduncle pigmentation, plant height (m), flower head diameter (cm), number of flowers per plant, number of petals, days from flower bud appearance to flowering, duration in days of flowering, number of leaves, leaf length (cm), leaf width (cm), head weight (g), seed weight of the main head (g), total seeds per plant (g), seeds in good condition (g), With this information collected from each sunflower variety, a multi-state matrix was made and standardized to obtain a correlation matrix, generating a dendrogram based on the distance of similarity, for which the SPSS statistical program was used, In the first sowing, 4 groups of comparisons were obtained where Music Bo presented a better result than the others, while in the second sowing, 5 groups of comparisons were presented where group 3 RussianG, Group 4 Moonwalk and Group 5 Moilinro, showed greater genetic variability, which in turn is useful for breeding programs since it can be attributed to high average values either in the height, diameter of the chapter, length and width of the seeds in comparison to the rest of the accessions, the principal component analysis was also performed, In the first and second sowing, both presented the same similarity in a positive and negative way in the first component, with a positive way the total seeds per plant (TSP), seeds in good condition (SBE), seed width (AS) and seed diameter (DS), while in a negative way the number of seeds per plant (TSP), seeds in good condition (SBE), seed width (AS) and seed diameter (DS), in component 2 of the first sowing, positively the number of flowers per plant (CFP) and the number of leaves (NH), in component 2 of the first sowing the duration in days to flowering (DF), leaf length (LH) and leaf width (AH) and negatively the number of flowers per plant (CFP) and plant height (AL) while in the second sowing with positive distribution the duration in days to flowering (DF), leaf length (LH) and leaf width (AH), leaf length (LH) and leaf width (AH), and with a negative distribution the number of leaves (NH), in component 3 of the first sowing, the number of petals (NP), days from the appearance of the flower bud to flowering (DBF) and plant height (AP) were positively distributed, while in the second sowing, peduncle pigmentation (PP) and plant height (AP) were positively distributed and the number of petals (NP) and days from the appearance of the flower bud to flowering (DBF) were negatively distributed, while in the second sowing, the fourth component was positively distributed and the number of petals (NP) and days from the appearance of the flower bud to flowering (DBF) were negatively distributed, the fourth component presented as positive the diameter of the capitulum (DC) and as negative the pigmentation of the peduncle (PP) and days from the appearance of the flower bud to flowering (DBF).
El girasol (Helianthus annuus L.) es una planta herbácea de la familia asterácea de gran importancia agrícola a nivel comercial por su atractiva inflorescencia y por su grande variedad de colores que van de amarillo clásico al anaranjado intenso y rojo, así mismo con su belleza al seguir al sol durante su desarrollo floral, convirtiendo el cultivo de girasol en una planta de gran valor ornamenta. El objetivo de este trabajo es, evaluar el comportamiento fenotípicos y agronómico de 8 variedades de “Helianthus annus” en el cantón Machala. El presente trabajo se realizó en el cantón Machala El Oro, realizando dos siembras de girasol el primero se llevó a cabo en el periodo de agosto a noviembre de 2020 y la segunda siembra en diciembre del mismo año a marzo de 2021 donde se cultivaron las variedades de girasol que fueron: Sunbright o Sunbeam, Moulin Rouge, Sunspot o Big Smile, Russian Giant, Velvet Queen, Common Sunflorwer, Music Box o Pastiche y Moonwalker, la zona de estudio cuenta con las coordenadas de longitud O79°57'37.91" latitud S3°15'31", se realizó 19 variables morfoagronómicas en el transcurso de su desarrollo, las cuales se caracterizaron mediante técnicas de análisis de crecimiento y las variables de rendimiento, se estimaron por medio de números y peso de cada capítulo y semillas, las variables a medir fueron: pigmentación del pedúnculo, altura de planta (m), diámetro del capítulo (cm), cantidad de flores por planta, número de pétalos, días de la aparición del botón floral hasta la floración, duración en días de la floración, número de hojas, largo de hojas (cm), ancho de hojas (cm), peso del capítulo (g), peso de semillas del capítulo principal (g), total de semillas por planta (g), semillas en buen estado (g), vana (g), peso de 100 semillas (g), largo de semilla (mm), ancho de semilla (mm) y diámetro de semillas (mm) con esta información recolectada que se tomó de cada variedad de girasol se realizó una matriz multiestado, con la que se procedió a estandarizar para obtener una matriz de correlaciones generando un dendrograma basado en la distancia de similitud para eso se empleó el programa estadístico SPSS, en ella se observó la diferencia de las dos siembras que se llevó a cabo por lo tanto se obtuvo, en la primera siembra 4 grupos de comparaciones donde la Music Bo, presenta un mejor resultado a diferencia de las demás, mientras que en la segunda siembra presentó 5 grupos de comparaciones donde el grupo 3 RussianG, Grupo 4 Moonwalk y el Grupo 5 Moilinro, presentaron mayor variabilidad genética que a su vez sirven para programas de fitomejoramiento ya que puede atribuirse a valores promedios altos ya sea en la altura el diámetro del capítulo, el largo y ancho de las semilla en comparación al resto de las accesiones, también se realizó el análisis de componentes principales, en el que se obtuvo que las primer siembra presentando 3 componentes mientras que en la segunda presentó 4 componentes, en la primera y segunda siembra ambas presentaron una misma similitud de forma positiva y negativa en el primer componente, con forma positiva el total de semillas por planta (TSP), semillas en buen estado (SBE), ancho de semill (AS) y diámetro de semillas (DS), mientras que de forma negativa la cantidad de flores por planta (CFP) y el número de hojas (NH), en el componente 2 de la primera siembra en forma positiva la duración en días de la floración (DF), largo de la hoja (LH) y el ancho hojas (AH) y de forma negativa la cantidad de flores por planta (CFP) y la altura de planta (AL) mientras que la segunda siembra con distribución positiva la duración en días de floración (DF), largo de hojas (LH) y el ancho de hojas (AH), y con una distribución negativa el número de hojas (NH), en el componente 3 de la primera siembra de forma positiva presenta el número de pétalos (NP) días de la aparición del botón floral hasta la floración (DBF) y de forma negativa altura de planta (AP) mientras que en la segunda siembra presenta de forma positiva la pigmentación del pedúnculo (PP) y la altura de la planta (AP) como forma negativa el número de pétalos (NP) y días de la aparición del botón floral hasta la floración (DBF) mientras que en la segunda siembra, el cuarto componente presentó de forma positivas el diámetro del capítulo (DC) y de forma negativa la pigmentación del pedúnculo (PP) y días de la aparición del botón floral hasta la floración (DBF). Siendo estos recursos de gran importancia para el desarrollo de nuevos cultivares de girasol.
Keywords: EVALUACIÓN; GENOTIPOS; AGRUPACIÓN; SIMILITUD